Deviasi pada Ekranisasi Novel “99 Cahaya di Langit Eropa” Karya Hanum Salsabiela Rais dan Rangga Almahendra - Priyatno, Isnan Adi; Kusumaningrum, Endah; Efendi, Agik Nur (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
This study aims to describe the deviation of the plot in the ecranization of the novel 99 Cahaya di Langit Eropa into a film. The method used in this research is descriptive analysis. The approach used in this research is a structural and intertextual approach. The intertextual approach makes it possible to determine the differences and similarities of the aspects studied. The data sources of this research are the novel and film 99 Cahaya di Langit Eropa, while the data in this research is in the form of text containing the plot in the novel 99 Cahaya di Langit Eropa and dialogue containing the plot in the film 99 Cahaya di Langit Eropa. Data collection is done by recording and classifying the data. Data analysis is done by interpreting the data and drawing conclusions. The results of this study are the deviation of the plot in the novel 99 Cahaya di Langit Eropa ecranization into a film in the form of shrinking the plot, adding plots, and varying changes in the plot.